On Structuring the Currency Composition of External Debt Portfolios - Torsten Amelung; Thorsten Mehltretter; Reinhard Solte (Asian Economies, 1986)
The paper develops criteria for the optimal currency composition of external debt for emerging and developing economies. The underlying theory is based on a portfolio model taking into account fluctuations of exchange rates and of export prices. In the ordinary portfolio approach, a country would expose itself deliberately to foreign exchange risk which might be manageeable in a situation of stable export prices. If export prices are subject to substantial fluctuations, the debt structure needs to be adjusted to the export structure. the empirical analysis for Korea shows that the dominant role of the USD as a major currency for foreign currency loans is inappropriate. Choosing a currency composition that would have been closer to the export structure would have been superior in terms of a strategy.
Additional information: The paper was first published as a Kiel Advanced Studies Working Paper of the Kiel Institute for the World Economy, Working Paper No. 43, October 1985
Keywords: H68; F47; H63; 330; Portfolio management of foreign debt; Managing of Balance-of-payments risks